Segunung Goes Digital: Application of Virtual Tour to Kampung Adat Segunung - A. Muammar Alawi; Arin Setiyowati; Praja Firdaus Nuryananda (Nusantara Science and Technology Proceedings, 2023)
Kampung Adat Segunung, is one of the fostered areas and the partners of the Faculty of Social and Political Sciences UPN "Veteran" Jawa Timur since 2022. The condition of Kampung Adat Segunung which has become a popular tourism destination in Jombang regency requires that village tourism must also be managed properly. Therefore, it is necessary to prepare adequate tourism infrastructure and superstructure. In this article the author has formulated two main problems, namely 1) the threat of urbanization by Segunung youths, and 1) the existence of a technological gap from the village government and the people of Kampung Adat Segunung with the development of information technology. As one of the community service activities, the author uses two methods, they are a) asset-based community development (ABCD) as a method of social approach to the community and b) virtual tour production with a soft skills approach. The community service activities in the Kampung Adat Segunung produce virtual tour technology that can be used as a medium for disseminating tourism information on the Kampung Adat Segunung to the wider community.